2010
DOI: 10.1209/0295-5075/92/30008
|View full text |Cite
|
Sign up to set email alerts
|

Record-breaking temperatures reveal a warming climate

Abstract: Abstract. -We present a mathematical analysis of records drawn from independent random variables with a drifting mean. To leading order the change in the record rate is proportional to the ratio of the drift velocity to the standard deviation of the underlying distribution. We apply the theory to time series of daily temperatures for given calendar days, obtained from historical climate recordings of European and American weather stations as well as re-analysis data. We conclude that the change in the mean tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
135
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(141 citation statements)
references
References 37 publications
6
135
0
Order By: Relevance
“…In 2009, Meehl et al [8] analyzed a large number of U.S. weather stations with respect to the occurrence of heat and cold records and found a significant effect of global warming in the ratio of the two of them. In 2010, Wergen and Krug [9] confirmed these findings in an independent study of European station and re-analysis data [57,80]. The work of Newman et al [10], Anderson and Kostinski [79], Elguindi et al [11] as well as Rahmstorf and Coumou [12] lead to similar results.…”
Section: Climate Recordsmentioning
confidence: 60%
See 4 more Smart Citations
“…In 2009, Meehl et al [8] analyzed a large number of U.S. weather stations with respect to the occurrence of heat and cold records and found a significant effect of global warming in the ratio of the two of them. In 2010, Wergen and Krug [9] confirmed these findings in an independent study of European station and re-analysis data [57,80]. The work of Newman et al [10], Anderson and Kostinski [79], Elguindi et al [11] as well as Rahmstorf and Coumou [12] lead to similar results.…”
Section: Climate Recordsmentioning
confidence: 60%
“…In a previous study, they analyzed historical temperature measurements from U.S. weather stations [57] that were recorded in whole degrees of Fahrenheit. They observed that this discreteness had a significant effect on the record statistics of the temperature data that could, in principle, disguise a possible effect of global warming on the occurrence of record-breaking events [9,40]. The problem is more general: In all applications, experimental measurements can only be recorded up to a certain accuracy.…”
Section: Rounding Effectsmentioning
confidence: 99%
See 3 more Smart Citations